Mild Oxidation of Benzylic Amines into Aldehydes Using an Oxidative Polonovski-Like Process - Desjardins, Samuel; Jacquemot, Guillaume; Canesi, Sylvain (Synlett, 2012)
A chemoselective and environmentally benign oxidation of benzylic amines into aldehydes mediated by a hypervalent iodine reagent has been developed. This mild oxidative version of the Polonovski process may be selectively carried out in the presence of several functionalities including a free alcohol and provides new synthetic opportunities as a masked aldehyde segment.
Keywords: hypervalent iodine; oxidation; amines; Polonovski; aromatic aldehydes